Implementation of an ergonomic program to increase productivity in the production area of a Peruvian footwear company - Cárdenas Vilcapoma , Jamil (2023)
Apply and implement an ergonomic plan to increase productivity in the production area of Lima Calzados, provide goals to avoid various health problems, reduce, eliminate or control safety risks and non-ergonomic goals such as forced positions, repetitive movements, etc. frequency of occupational diseases of the musculoskeletal system during use, thus providing employees with better quality of work and maximum performance with minimum effort in a safe and healthy environment. The purpose of this review is to develop an ergonomic procedure for the production area to assess the ergonomic risks of working in the production process using the R.E.B.A. It was. Protect people's health and improve the quality of work and life of employees. This study was carried out based on the PRISMA method used to develop research search engines such as GOOGLE ACADEMIC, REDALYC, SCIELO, SPRINGER LINK, PROQUEST and using the delimitation criteria used by the Mexican Journal of Ergonomics, Items and Anthropometry. bc book of the Mexican Society of Ergonomics (SEMAC). In this review, we will look further into the ergonomic risks for companies in the footwear industry, recognizing the importance of any worker committing to the procedures laid out in an ergonomics program, which will ultimately lead to higher productivity in the footwear industry. shoe companies.